#Fallism and alter-globalisation: South African student movements as multi-institutional responses to globalisation. (8th August 2019) - Garton, Paul M.
ABSTRACT: The South African student movements collectively referred to as #Fallism or #MustFall were more than resistance to fee increases. They were, and continue to be, movements targeting multiple institutions of Western coloniality and globalisation in tertiary education to establish economic and social equity, placing #Fallism within the broader global backlash against neoliberalism, neoconservativism, and Westernisation. This article makes three core claims: (1) modes of domination in globalisation are multi-institutional, thus alter-globalisation movements are also multi-institutional, (2) The goals of #Fallism in South Africa were, in part, related to alter-globalisation, and (3) #Fallism should be considered as a multi-institutional, alter-globalisation movement.